2011
DOI: 10.1002/hep.24160
|View full text |Cite
|
Sign up to set email alerts
|

Host apolipoprotein b messenger RNA-editing enzyme catalytic polypeptide-like 3G is an innate defensive factor and drug target against hepatitis C virus

Abstract: Host cellular factor apolipoprotein B messenger RNA (mRNA)-editing enzyme catalytic polypeptide-like 3G (hA3G) is a cytidine deaminase that inhibits a group of viruses including human immunodeficiency virus-1 (HIV-1). In the continuation of our research on hA3G, we found that hA3G stabilizing compounds significantly inhibited hepatitis C virus (HCV) replication. Therefore, this study investigated the role of hA3G in HCV replication. Introduction of external hA3G into HCV-infected Huh7.5 human hepatocytes inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 39 publications
0
42
0
1
Order By: Relevance
“…This resistant cluster includes many viral genomes, such as Human Herpesvirus 1 [31], and hepatitis C Virus [35]. Curiously, this cluster includes the Epstein-Barr Virus, suggesting that this virus may have evolved resistance to mutations by both APOBECs and AID.…”
Section: Resultsmentioning
confidence: 99%
“…This resistant cluster includes many viral genomes, such as Human Herpesvirus 1 [31], and hepatitis C Virus [35]. Curiously, this cluster includes the Epstein-Barr Virus, suggesting that this virus may have evolved resistance to mutations by both APOBECs and AID.…”
Section: Resultsmentioning
confidence: 99%
“…HCV virus stock was prepared as previously reported [37,38]. The African green monkey kidney cells (Vero), coxsackie viruses (Coxsackie virus B3 Nancy strain and Coxsackie virus B6 Schmitt strain) were acquired from the Institute of Virology, Chinese Academy of Preventive Medicine (Beijing, China).…”
Section: Biological Assaysmentioning
confidence: 99%
“…Considering that A3G targets ssDNA, such lack of hypermutation is expected for HCV, which presents exclusively RNA as genomic material during all phases of its replication. Interestingly, it has also been shown that the presence of exogenous HIV-1 Vif led to an intracellular decrease of A3G and consequently to an increase of HCV replication, suggesting the involvement of Vif in the HIV-1/HCV coinfection [220]. …”
Section: Role Of Apobec Enzymes On Different Human Viral Infectionsmentioning
confidence: 99%
“…Treatment of HCV-infected Huh7.5 cells with two stabilizing components of APOBEC3G, which increased its intracellular levels, inhibited HCV replication [220]. …”
Section: Role Of Apobec Enzymes On Different Human Viral Infectionsmentioning
confidence: 99%